Establishing the Minimal Clinically Important Difference, Substantial Clinical Benefit, and Patient Acceptable Symptomatic State following Primary Medial Patellofemoral Ligament Reconstruction. Issue 7 (31st July 2020) - Huddleston, Hailey; Naveen, Neal; Southworth, Taylor; Nwachukwu, Benedict; Cole, Brian; Yanke, Adam; Walsh, Justin
Objectives: Medial patellofemoral ligament (MPFL) reconstruction is an effective surgical procedure for patients with recurrent lateral dislocations. Outcome measurements can identify the success of a surgical procedure but are shifting away from absolute values or deltas of patient-reported outcomes (PROs) towards the minimal clinically important difference (MCID), substantial clinical benefit (SCB), and patient acceptable symptomatic state (PASS), representing the smallest clinical improvement that patients perceive as important, the threshold at which patients notice a considerable improvement, and patient satisfaction with their outcome, respectively. To our knowledge no prior study has defined these thresholds in MPFL reconstruction patients. Methods: An institutional database was reviewed for patients who underwent primary MPFL reconstruction between August 2015 to February 2018 with a minimum 6-month follow-up. IKDC, Kujala and KOOS were administered to all patients pre-operatively and at 6-months and 1-year post-operatively. An anchor-based approach with a receiver-operator curve/area under the curve analysis using the Youden index was performed to calculate the MCID, SCB and PASS. The predictive power was determined to be acceptable with AUC≥70% and excellent with AUC≥80%. Results: From 2015 to 2018, 93 of 162 patients (mean age 23.7±10.1 years; 25 males, 68 females) completed for 6-month follow-up. At 6-months follow-up, SCB and PASS were defined with acceptable predictive power for all scores listed, while MCID achieved this for KOOS pain and sports subscores only (Table 1). At 1-year follow-up, SCB and PASS were each defined with acceptable predictive power for all scores listed, while MCID achieved this mark for KOOS pain and quality of life subscores as well as both Kujala scales. Conclusion: This study establishes MCID, SCB and PASS for IKDC, Kujala, and KOOS subscores at 6-months and 1-year postoperatively with excellent predictive power for 19/23 PROMs investigated at 1-year. These findings represent important benchmarks in patients undergoing primary MPFL reconstruction.